Interpretation and Performance Practice on Debussy’s Ballade - Akepiriya, Supatcha; Chulapan, Panjai (Rangsit Music Journal, 2022)
This research article is about interpretation and performance practice of Ballade composed by Claude Debussy (1862-1918). The research aims to develop a beautiful sound in performance of Ballade piece and create a practice plan for piano recital. The composition, composed early in Debussy’s career, contains flexible and beautiful melodies. The pianist needs to control sound qualities as well as other musical elements. Difficult techniques for a performer are keeping the equal tones together with pushing the melodies forward throughout the whole time. The researcher studied the interpretations and practiced with appropriate techniques in order to meet the composer’s purpose. The result of the study shown that the performer has to control sound quality as well and use different techniques for each section together with practice properly for good at perform the music in order to meet the composer’s purpose as much as possible.